Pengaruh Kualitas Produk, Kualitas Pelayanan, dan Persepsi Harga terhadap kepuasan Pelanggan di Royal Kuningan Hotel - mike agusli mike; Salman Paludi (LPPM Universitas Asa Indonesia, 2022)
Thisaresearch aims to analyzeathe influence ofaproduct quality, service quality, and price perception on customer satisfaction. This research was conducted at Royal Kuningan Hotel by disseminating quesioner to 100 respondents. The sample techniqueaused in thisastudy is a purposive samplingatechnique. While the method used in this studyais a multiple linear regression method. Then the results of product research have a positive and significant influence of 9.06% oncustomer satisfaction. Then the quality of service has a positiveaand significant effect of 21.99% on customer satisfaction. While the price perception has no positive and insignificant effect of 3.20% on customer satisfaction. Thus Simultaneously (simultaneously) product quality, servicequality, andaprice perception have a positive and significant influence of 31.02% on customer satisfaction. While the remaining 68.98% of othersavariables not included in this study.